2005
DOI: 10.1038/sj.jcbfm.9600116
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Stroke

Abstract: Inhibitors of HMG-CoA reductase (statins) are potent cholesterol-lowering drugs. Large clinical trials have shown that statins reduce the incidence of cerebrovascular events, which might be surprising because cholesterol is not an established risk factor for stroke. In addition to their cholesterollowering properties, statins exert a number of pleiotropic, vasculoprotective actions that include improvement of endothelial function, increased nitric oxide (NO) bioavailability, antioxidant properties, inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
112
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(120 citation statements)
references
References 167 publications
(135 reference statements)
4
112
1
3
Order By: Relevance
“…At the same time, by modeling of stroke in animal experiments, our understanding of the pathophysiologic mechanisms by which focal cerebral ischemia kills brain cells has greatly improved (Lo et al, 2003;Dirnagl et al, 1999). In addition, experimental stroke studies have identified numerous therapeutic targets for stroke therapy (Dirnagl et al, 2003;Meisel et al, 2005;Endres, 2005;Lo et al, 2005;Lindvall and Kokaia, 2004). However, it is an overall failure to validate the efficacy of such treatment strategies, which is fuelling a debate concerning the general predictive value of experimental modeling of this complex disorder (Hoyte et al, 2004;Fisher and Tatlisumak, 2005;Kaste, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, by modeling of stroke in animal experiments, our understanding of the pathophysiologic mechanisms by which focal cerebral ischemia kills brain cells has greatly improved (Lo et al, 2003;Dirnagl et al, 1999). In addition, experimental stroke studies have identified numerous therapeutic targets for stroke therapy (Dirnagl et al, 2003;Meisel et al, 2005;Endres, 2005;Lo et al, 2005;Lindvall and Kokaia, 2004). However, it is an overall failure to validate the efficacy of such treatment strategies, which is fuelling a debate concerning the general predictive value of experimental modeling of this complex disorder (Hoyte et al, 2004;Fisher and Tatlisumak, 2005;Kaste, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Statins achieve their main effect via the inhibition of the enzyme 3-hydroxy-3-methyl-glutaryl-CoA reductase, decreasing the synthesis of cholesterol and isoprenoids, and upregulating the production of endothelial nitric oxide synthase. 13,14 There is also decreased production of nicotinamide dinucleotide phosphate oxidase that results in fewer free oxygen radicals in the systemic circulation. 13 By inhibiting L-mevalonic acid synthesis, statins decrease the amount of isoprenoid intermediates that have a direct role in intracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 There is also decreased production of nicotinamide dinucleotide phosphate oxidase that results in fewer free oxygen radicals in the systemic circulation. 13 By inhibiting L-mevalonic acid synthesis, statins decrease the amount of isoprenoid intermediates that have a direct role in intracellular signaling. This, in turn, has a positive impact on inflammation, cell proliferation, and vasodilatation ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with elevated levels of triglycerides and LDLs are at risk of myocardial infarction and/or cerebral vascular accident (stroke), although the role of cholesterol as a stroke risk factor is less clear. [5] It is clear that elevated blood cholesterol level is a major risk factor for CHD, [6] and many studies have shown that the risk of CHD events can be reduced by lipid-lowering therapy. [7] Prior to 1987, the lipid-lowering armamentarium was limited essentially to consumption of a low saturated fat and cholesterol diet, the bile acid sequestrants cholestyramine and colestipol, nicotinic acid (niacin), the fibrates and probucol.…”
Section: Introductionmentioning
confidence: 99%
“…[10] These include improvement of endothelial function, enhancement of the ischemic vasodilatory response, protection from ischemia-reperfusion injury, increased nitric oxide bioavailability, antioxidant properties, inhibition of inflammatory responses, immunomodulatory actions, regulation of progenitor cells and stabilization of atherosclerotic plaques. [5,11] The statin drugs known as hypolipidemic drugs have recently been examined for their usefulness in the treatment of the conditions such as osteoporosis, Alzheimer's disease, [12] cardiac diseases, organ transplantation, stroke and diabetes. [13] The synergism of statins with other drugs can also be useful in reducing the incidence of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%